The mysterious howling (Incorrigible children of Ashton Place, 1, 1, 2015)
Fifteen-year-old Miss Penelope Lumley, a recent graduate of the Swanburne Academy for Poor Bright Females, is hired as governess to three young children who have been raised by wolves and must teach them to behave in a civilized manner quickly, in preparation for a Christmas ball.

The hidden gallery (Incorrigible children of Ashton Place, 2, 1, 2015)
Fifteen-year-old Miss Penelope Lumley, a governess trained at the Swanburne Academy for Poor Bright Females, takes the three Incorrigible Children of Ashton Place to London, England, and learns they are under a curse.

The unseen guest (Incorrigible children of Ashton Place, 3, 1, 2015)
"Miss Penelope Lumley embarks on an investigation into the mysteries surrounding the Incorrigible children, Lord Ashton, the forests of Ashton Place, and her own past"--

Charlotte Bronte's Jane Eyre (Calico illustrated classics, ,, 2012)
In early nineteenth-century England, an orphaned young woman accepts employment as a governess at Thornfield Hall, a country estate owned by the mysteriously remote Mr. Rochester.

Little Miss Bronte: Jane Eyre :a counting primer (Babylit books, , 1, 2012)
Counts from one to ten using characters, places, and events from Charlotte Bronte's "Jane Eyre." On board pages.

Journey to the river sea (Puffin Books, Puffin, 2003)
Sent with her governess to live with the dreadful Carter family in exotic Brazil in 1910, Maia endures many hardships before fulfilling her dream of exploring the Amazon River. Accompanied by Miss Minton, a fierce-looking, no-nonsense governess, Maia, a young orphan, sets off for the wilderness of the Amazon, expecting curtains of orchids, brightly colored macaws, and a loving family. But what she finds is an evil-tempered aunt and uncle and their spoiled daughters. It is only when she is swept up in a mystery involving a young Indian boy, a homesick child actor, and a missing inheritance that Maia lands in the middle of the Amazon adventure she's dreamed of. Readers of every generation will treasure Ibbotson's lush historical adventure that harkens back to the beloved classics of Frances Hodgson Burnett and Louisa May Alcott.